TWO NEW SPECIES OF PREDATORY MITES (ACARINA : PHYTOSEIIDAE) FROM KERALA (INDIA) - ANITHALATHA, MARY (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2005)
Two new species of predatory mites of the family Phytoseiidae viz. Amblyseius (Amblyseius) mohanasundarami sp. nov. and A. (A.) koothaliensis sp. nov. are described with appropriate illustrations.